Upaya Orang Tua Dalam Meningkatkan Perkembangan Dan Bahasa Anak Usia 5 Tahun - Sariwati Muhamad (Peneliti.net, 2023)
This research was conducted with the aim of knowing parents' efforts to improve children's development and language. The method used in this study is a qualitative method, using interviews to obtain the data. There were 2 participants in this study, namely parents of children aged 5 years. The results of this study indicate that the main factors influencing children's development and language are environmental factors, namely the family environment. For this reason, this research shows that parents' efforts to improve children's development are through giving nutritious food, developing inheritance from birth (potential), exploring, solving problems themselves, giving praise. While efforts to develop children's language consist of providing stimulus, giving them space to play, using media in learning, providing YouTube Kids which contains useful children's videos, repeating words to children, and asking lots of questions